Optimal Tissue Reperfusion Estimation by Computed Tomography Perfusion Post-Thrombectomy in Acute Ischemic Stroke. Issue 12 (December 2021) - Tan, Zefeng; Parsons, Mark; Bivard, Andrew; Sharma, Gagan; Mitchell, Peter; Dowling, Richard; Bush, Steven; Xu, Anding; Yan, Bernard
Abstract : Background and Purpose: Modified Thrombolysis in Cerebral Infarction score (mTICI) ≥2b is defined as successful reperfusion. However, mTICI has rarely been correlated with dynamic perfusion imaging postendovascular therapy for acute stroke. We aimed to study the proportion of tissue optimal reperfusion (TOR) postendovascular therapy across different grades of mTICI. Methods: We conducted a single-center retrospective analysis of patients with acute ischemic strokes who had endovascular therapy between 2018 and 2019. Computer tomography perfusion or magnetic resonance perfusion was performed before and after endovascular therapy. Tmax+6 volume reduction of >90% was defined as TOR. Comparisons of proportions of TOR in different grades of mTICI were performed. In the present study, the requirement for informed consents was waived. Results: Eighty-two patients were included. The difference in the proportion of TOR for TICI categories was statistically significant (mTICI score 0, 0%, mTICI score 2A, 0%, mTICI score 2b, 50.0%, mTICI score 2c, 80.0%, mTICI score 3, 81.3%, χ 2 =14.035, P =0.003). Multivariable logistic regression showed that lower age (odds ratio, 0.932, P =0.017), onset-to-tissue-type plasminogen activator time (odds ratio, 0.980, P =0.005) and TOR (odds ratio, 8.764, P =0.031) were associated with favorable functional outcome. Conclusions: The proportion of TOR achieved by mTICI score of 2b was significantly lower than mTICI score of 2c and mTICI score of 3. TOR was associated with favorable functional outcome, and the degree of reperfusion was more strongly correlated with outcomes than the mTICI scores. Abstract : Supplemental Digital Content is available in the text.